Caffeine does not affect susceptibility to cortical spreading depolarization in mice. Issue 4 (April 2019) - Yalcin, Nilufer; Chen, Shih-Pin; Yu, Esther S; Liu, Tzu-Ting; Yen, Jiin-Cherng; Atalay, Yahya B; Qin, Tao; Celik, Furkan; van den Maagdenberg, Arn MJM; Moskowitz, Michael A; Ayata, Cenk; Eikermann-Haerter, Katharina
Several factors that modulate migraine, a common primary headache disorder, also affect susceptibility to cortical spreading depolarization (CSD). CSD is a wave of neuronal and glial depolarization and thought to underlie the migraine aura and possibly headache. Here, we tested whether caffeine, known to alleviate or trigger headache after acute exposure or chronic use/withdrawal, respectively, modulates CSD. We injected C57BL/6J mice with caffeine (30, 60, or 120 mg/kg; i.p.) once ( acute ) or twice per day for one or two weeks ( chronic ). Susceptibility to CSD was evaluated by measuring the electrical CSD threshold and by assessing KCl-induced CSD. Simultaneous laser Doppler flowmetry was used to assess CSD-induced cortical blood flow changes. Recordings were performed 15 min after caffeine/vehicle administration, or 24 h after the last dose of chronic caffeine in the withdrawal group. The latter paradigm was also tested in mice carrying the familial hemiplegic migraine type 1 R192Q missense mutation, considered a valid migraine model. Neither acute/chronic administration nor withdrawal of caffeine affected CSD susceptibility or related cortical blood flow changes, either in WT or R192Q mice. Hence, adverse or beneficial effects of caffeine on headache seem unrelated to CSD pathophysiology, consistent with the non-migrainous clinical presentation of caffeine-related headache.